Teoria da solução inventiva de problemas integrada à produção mais limpa - Kubota, Flávio Issao (2012)
The search for innovative solution, aligned to the growing need for cleaner industrial operations, is a solving problem process. In addition, we emphasize that the dairy industry has significant importance to the regional, national and global economy, since Brazil is one of the worldwide largest milk producers, while Rio Grande do Sul is one of the largest national producers. Hence, this research aimed to use the Theory of Inventive Problem Solving (TRIZ) as a support tool to solve problems related to Cleaner Production (CP), serving as an innovative tool towards sustainability and higher environmental efficiency. The research involved three different companies. The study was based on the TRIZ fundamental concepts and function analysis, in order to describe the critical processes in the surveyed industries, aiming to detail the features that influence the quality of the studied processes. The results showed that TRIZ can be an alternative to be considered for solving CP problems, especially in situations where exists a scarcity of available data by companies. Also, we highlighted the need of CP feasibility analysis, since TRIZ method does not include this step. Therefore, the proposed inventive solutions are attractive technically, environmentally and economically, meeting the needs of each company studied. Thus, we can conclude that the integration of TRIZ to CP is effective in generating opportunities for inventive and sustainable solutions.